2007
DOI: 10.1021/bm061018q
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Copolyesters Containing Poly(l-lactide) and Poly(hydroxyalkanoate) Units

Abstract: In situ copolyesters containing polylactide (PLA) and polyhydroxyalkanoate (PHA) segments were obtained via ring-opening polymerization of L-lactide using PHA as a macroinitiator with stannous octoate as catalyst. Incorporation of PHA (20 wt %) into PLA affords a novel copolymer with Mn values ranging from 25 to 50 KDa and low polydispersities of 1.8-2.3. DSC analysis of the copolymer indicates well-defined crystallization and melting transitions different from the homopolymers and corresponding blend. The pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…However, the relatively poor impact and heat resistance of the material are considered to be a crucial weak point blocking a wider range of applications. Thus, PLAs are an active area of research into improving their properties, for example, by the addition of plasticizers, blending with other polymers, copolymerizations and various chemical modifications, as may be seen in the large number of reports and patents (Haynes et al, 2007;Noda et al, 2004;Ozkoc and Kemaloglu, 2009;Pillin et al, 2006;Younes and Cohn, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relatively poor impact and heat resistance of the material are considered to be a crucial weak point blocking a wider range of applications. Thus, PLAs are an active area of research into improving their properties, for example, by the addition of plasticizers, blending with other polymers, copolymerizations and various chemical modifications, as may be seen in the large number of reports and patents (Haynes et al, 2007;Noda et al, 2004;Ozkoc and Kemaloglu, 2009;Pillin et al, 2006;Younes and Cohn, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the synthesis of copolymers, containing LA and 3HA units, by the ring-opening copolymerization of (S,S)-lactide and (R)-b-butyrolactone and the ring-opening copolymerization of (S,S)-lactide using PHA as a macroinitiator. The synthesized copolymers have better properties than those of PLA homopolymer (16,17).…”
mentioning
confidence: 93%
“…It is a very attractive material, but its application is limited in part due to its brittle properties, such as poor elongation, slow crystallization rate, and so on. One of the methods to improve the properties of PLA is copolymerization (Abe et al 1997;Haynes et al 2007) with another repeating unit. For example, Abe et al and Haynes et al (Abe et al 1997;Haynes et al 2007) reported the synthesis of copolymers containing LA and 3HA units by the ring-opening copolymerization of (S, S)-lactide with (R)--butyrolactone and by the ring-opening copolymerization of (S, S)-lactide using PHA as a macroinitiator.…”
Section: Introductionmentioning
confidence: 99%
“…One of the methods to improve the properties of PLA is copolymerization (Abe et al 1997;Haynes et al 2007) with another repeating unit. For example, Abe et al and Haynes et al (Abe et al 1997;Haynes et al 2007) reported the synthesis of copolymers containing LA and 3HA units by the ring-opening copolymerization of (S, S)-lactide with (R)--butyrolactone and by the ring-opening copolymerization of (S, S)-lactide using PHA as a macroinitiator. The synthesized copolymers had better properties than those of the PLA homopolymer (Abe et al 1997;Haynes et al 2007).…”
Section: Introductionmentioning
confidence: 99%